2018
DOI: 10.1111/cas.13771
|View full text |Cite
|
Sign up to set email alerts
|

Wnt signaling in human and mouse breast cancer: Focusing on Wnt ligands, receptors and antagonists

Abstract: Wnt proteins, a group of secreted glycoproteins, mainly combine with receptors Frizzled (FZD) and/or low‐density‐lipoprotein receptor‐related proteins 5/6 (LRP5/6), initiating β‐catenin‐dependent and ‐independent signaling pathways. These pathways, which can be regulated by some secreted antagonists such as secreted Frizzled‐related proteins (SFRP) and dickkopf‐related protein (DKK), play a critical role in embryo development and adult homeostasis. Overactivation of Wnt signaling has been implicated in some hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(56 citation statements)
references
References 76 publications
1
53
0
Order By: Relevance
“…In agreement with the above findings, the pathway analysis of the gene expression data in this study showed enrichment of WNT (both canonical and non-canonical) pathways, the planar cell polarity (PCP) pathway, and signaling pathways regulating the pluripotency of stem cells in DCIS (generally induced by WNT signaling). The Wnt signaling pathway is known to promote cancer progression, metastasis, and is involved in EMT [48]. EMT is essential in tumor invasion because it reduces cell-cell adhesion and increases cell motility.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with the above findings, the pathway analysis of the gene expression data in this study showed enrichment of WNT (both canonical and non-canonical) pathways, the planar cell polarity (PCP) pathway, and signaling pathways regulating the pluripotency of stem cells in DCIS (generally induced by WNT signaling). The Wnt signaling pathway is known to promote cancer progression, metastasis, and is involved in EMT [48]. EMT is essential in tumor invasion because it reduces cell-cell adhesion and increases cell motility.…”
Section: Discussionmentioning
confidence: 99%
“…MMTV-Wnt1, MMTV-Wnt10b and MMTV-βcatΔN transgenic mice have clearly demonstrated that canonical Wnt/β-catenin pathway has the capacity to induce BC development [22]. In human BC, Wnt10b, but not Wnt1, as well as Fzd7 and Wnt co-receptor LDL receptor-related proteins 6 (LRP6) was overexpressed in TNBC, with activation of β-catenin pathway [7,[23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…The Wnt pathway is one of the most important pathways regulating the development of breast cancer [43], andβ-catenin is a key regulator of the Wnt pathway. This pathway is not active in normal mature cells.…”
Section: Discussionmentioning
confidence: 99%